2016
DOI: 10.3233/jad-151150
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Effects of Multisensory Stimulation and Individualized Music Sessions on Elderly People with Severe Dementia: A Randomized Controlled Trial

Abstract: The objective of this study was to compare the effects of a multisensory stimulation environment (MSSE) and individualized music sessions on agitation, emotional and cognitive status, and dementia severity in a sample of institutionalized patients with severe dementia. Twenty-two participants with a diagnosis of severe or very severe dementia were randomly assigned to two groups: MSSE and individualized music sessions. Both groups participated in two 30-min weekly sessions over 16 weeks. Outcomes were agitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
99
3
12

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(124 citation statements)
references
References 55 publications
4
99
3
12
Order By: Relevance
“…Further data extraction of 141 full‐text articles excluded 135 papers based on the inclusion criteria. Although six papers met the inclusion criteria, three papers were from the same research project as confirmed by the study author . Thus, a total of four studies were included in this review as shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Further data extraction of 141 full‐text articles excluded 135 papers based on the inclusion criteria. Although six papers met the inclusion criteria, three papers were from the same research project as confirmed by the study author . Thus, a total of four studies were included in this review as shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Music was played through a compact disc (CD) player or a computer in the participant's room, in a private/quiet room or a familiar area. Trained professionals and a research assistant delivered the intervention. In one study, it was stated only that the participants passively listened to their preferred music, while in another study, the music therapist prepared the music playlist but the participants listened to the music without interaction with the therapist .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The result showed that the multisensory environment had a better effect on anxiety than the music sessions. As for agitation, both groups had improved results [20]. However, Raglio et al [21] showed a different result.…”
Section: Individual Music Therapymentioning
confidence: 87%